Keberadaan Silek Pangean Batino di Nagari Tanjung Lolo Kecamatan Tanjung Gadang Kabupaten Sijunjung - Azizah, Srida Yena; Yurisman, Yurisman; Endrizal, Endrizal (Pusat Kajian Pancasila Universitas Negeri Padang, 2023)
This research discusses the existence of silek Pangean Batato in Nagari Tanjung Lolo. This study uses qualitative methods with data collection techniques by observation, interviews and documentation. The theory used in this thesis is Jeun Paul Satre's Existentialism theory. The results of this study indicate that the existence of silek pangean Batino discusses the history of silek pangean Batino at the Malin Batuah Nagari Tanjung Lolo website, the differences between Silek Pangean Batino and Silek Pangean Jantan, organizational structure of Malin Batuah College/Laman, characteristics of silek Pangean College, and the moves that characterize typical of the Pangean silek college on the Malin Batuah site. The development of silek Pangean Batato in Nagari Tanjung Lolo includes the beginning of the existence of Silek Pangean in Nagari Tanjung Lolo, the development of Silek Pangean, the physical condition of the pages of Pangean Batato, and Silek Pangean Batato in several activities. In terms of the values contained in silek Pangean Batato are spiritual values, which are divided into truth values, religious values, moral/ethical values.